1997
DOI: 10.1111/1468-0009.00069
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Integrated Rural Health Networks

Abstract: In an era of constraints on public and private sector health care budgets, organizational restructuring of hospital and physician practice, and the shifting of financial risk to patients and providers, rural health professionals and communities are grappling with the issue of how to assure access to a comprehensive and affordable set of health care services. In recent years, rural health providers have turned to the strategy of developing voluntary network relations as an alternative to system or diversificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Defining a network is not straightforward in the rural context (104); Moscovice and colleagues have been explicit in their definition and have used it to create a characterization of network structures in and involving rural communities (59). Their study found that networks are widespread, 42% of rural hospitals are involved in some alliance or network, and more than half of the formal networks involve an urban institution (58). Hospitals joined these networks to gain financial advantages, to access resources, and to gain operational assistance from partners (104).…”
Section: Network and Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Defining a network is not straightforward in the rural context (104); Moscovice and colleagues have been explicit in their definition and have used it to create a characterization of network structures in and involving rural communities (59). Their study found that networks are widespread, 42% of rural hospitals are involved in some alliance or network, and more than half of the formal networks involve an urban institution (58). Hospitals joined these networks to gain financial advantages, to access resources, and to gain operational assistance from partners (104).…”
Section: Network and Systemsmentioning
confidence: 99%
“…Rural places felt these changes in ways other than through the dominance of markets by managed-care companies because there were fewer opportunities for cost savings or profit enhancement owing to the nature of rural markets (16). Rural health care changed more as a result of the increased integration and assimilation of professionals and institutions into systems and networks (58). The pressure of reform across the wider market resulted in important government policy changes for rural health 0163-7527/00/0510-0639$14.00 ?…”
Section: Introductionmentioning
confidence: 99%
“…The principles of organizational integration described by Shortell et al (Conrad and Shortell 1997;Shortell, Gillies, Anderson, et al 1993;Shortell, Gillies, and Anderson 1994) come from a perspective within the traditional medical system and focus on the relationships between hospitals, physician groups, and other providers of medical/pharmacy/laboratory services. The framework of system integration described by Moscovice et al (Moscovice, Wellever, Christianson, et al 1997) focuses on the unique institutions and organizational relationships required for a rural medical care network. The Community Care Network takes a broad public health perspective that focuses on the role of hospitals and physicians in improving population health (American Hospital Association 1995;Catholic Hospital Association 1993;Kindig 1997).…”
Section: Organizational Integration and Integrated Child Developmentmentioning
confidence: 99%
“…Nearly half were networks of hospitals only, and approximately 70 percent had existed for less than four years (Moscovice, Wellever, Christianson, et al 1997). Rural networks can help providers overcome natural barriers to participating in managed care plans and other alternative nancing and service delivery arrangements.…”
Section: Literature Review/theoretical Expectationsmentioning
confidence: 99%